Preditores urinários de sepse neonatal tardia - Costa, Daniela Silva Rodrigues da (2017)
Introduction: Neonatal sepsis is one of the main causes of morbimortality in the Neonatal Intensive Care Units, and the difficulty in its early diagnosis has led to the excessive use of antibiotics and the emergence of resistant microorganisms. The search for new biochemical markers, that are capable to early predict the risk of developing sepsis, has been the subject of many studies, especially urinary biomarkers, which are collected safely and non-invasively. The objective of this study was to evaluate developing neonatal sepsis in very low birth weight preterm infants, using urinary biomarkers. Method: The study was performedincluded newborns with gestational age less than 34 weeks and birth weight less than 1500 grams. Urine collection was performed between 48-72h of life and 27 biomarkers were dosed. The study included newborns younger than 34 weeks gestational age and birth weight less than 1500 grams. The included newborns were divided into two groups according to the evolution of each: GC - control group (did not develop sepsis) and GS - a study group (developed late sepsis). Results: 35 newborns were evaluated, 12 of the CG and 23 of the GS. The results showed a statistically significant early elevation in 11 GS biomarkers in relation to the CG (IL-4 (p = 0.042), IL-5 (p = 0.039), IL-7 (P = 0.015), IL-15 (p = 0.015), IL-17A (p = 0.009), TNF-α (p = 0.015), MiP- 0.021) and G-CSF (p = 0.009)). Mechanical ventilation was the only clinical variable that presented a statistically significant association with 6 of these 11 biomarkers (IL-5 p = 0.04, IL-7 p = 0.02, IL-15 p = 0.03, IL-17A p = 0.03, MiP-1 p = 0.02 and G-CSF p = 0.04)Conclusion: Urine is a promising fluid in the dosage of biomarkers and with great potential for the evaluation of the risk of neonatal sepsis. The early increase in the urine of these cytokines suggests that these can be used as predictors of late neonatal sepsis.